Treatment of children with refractory/relapse high risk langerhans cell histiocytosis with the combination of cytarabine, vindesine and prednisone - Wenqian Wang; Jian Ge; Honghao Ma; Hongyun Lian; Lei Cui; Yunze Zhao; Zhigang Li; Tianyou Wang; Rui Zhang (BMC, 2024)
Abstract Background The patients with multisystem and risk organ involvement Langerhans cell histiocytosis (MS-RO + LCH) have poor prognosis. The patients with MS-LCH who failed front-line therapy have a high mortality rate and the standard salvage treatment has not been established. The combination of cytarabine (Ara-c), vincristine (VCR) and prednisone might be effective for refractory/relapse MS-RO + LCH, with low toxicity. Methods We retrospectively analyzed pediatric refractory/relapse MS-RO + LCH patients treated with the low-dose Ara-c (100mg/m2/d×5days) or high-dose Ara-c (500mg/m2/d×5days) combined with vindesine (VDS) and prednisone in a single center. The efficacy, outcomes and adverse events were analyzed. Results From January 2013 to December 2016, 13 patients receiving the low-dose Ara-c chemotherapy (LAC) and 7 patients receiving the high-dose Ara-c chemotherapy (HAC) were included in the study. 11 (84.6%) of the 13 patients treated with the LAC regimen and 6 (85.7%) of the 7 patients treated with the HAC regimen had response after four courses of the therapy. All patients in the study were alive during follow-up and the 3-year event-free survival rate (EFS) was 53.7% and 85.7% in the LAC and HAC groups. The most frequent adverse event was Grade 1/2 myelosuppression, which was observed in 38.5% (5/13) and 42.9% (3/7) of the patients receiving the LAC and HAC regimen. Conclusions A combination of Ara-c, VDS and prednisone was effective and safe for some patients with refractory/relapse MS-RO + LCH. The high-dose Ara-c regimen was associated with a numerically higher EFS rate.